Upgrading and Migrating to BizTalk Server 2016 - Beckner, Mark; Jones, Dylan (De|G Press, 2017)
There are a variety of considerations you'll need to take into account when migrating your solutions to BizTalk 2016. In this book, you'll find detailed information about how to migrate your components "as-is", as well as recompile them with the latest version of Visual Studio. You'll look at ways to improve your components pre-migration, as well as troubleshoot issues within these components. You'll learn how to make intelligent mapping updates, especially with XSLT, and how to simplify your overall architecture. Additionally, working with BizTalk 2016 in an Azure environment and building BizTalk Azure Services are covered. Readers will look at migrating maps, orchestrations, .NET assemblies, database components, EDI parties and configurations, and other artifacts found in BizTalk solutions. They will also be able to quickly come to an understanding of what will be involved in a migration and what will be required for resourcing and costs associated with a migration. Readers will find information that will cover virtually every aspect of their upgrade to BizTalk 2016, and should come away with a simpler solution once that migration is complete.